(untitled) - Henri Cohen (New York, 1996)
The book describes 148 algorithms that are fundamental for number-theoretic computations including computations related to algebraic number theory, elliptic curves, primality testing, and factoring. The detailed description of each algorithm allows immediate computer implementation; numerous further hints for implementation are also provided. The book also gives a survey of factoring and primality testing methods, including a detailed description of the number-field sieve algorithm. It ends with a description of available computer package and some useful tables. It contains a large number of exercises
Keywords: algebraic number theory